Carbon fiber reinforced titanium-based composite material and preparation method thereof

Through the electrochemical etching and microwave sintering technology of modified and recovered carbon fibers, carbon fiber reinforced titanium-based composite materials are formed, which solves the problems of insufficient application of recycling carbon fibers in titanium-based composite materials in the prior art and low traditional heating efficiency, and realizes the problem of The preparation of high-strength and high-ductility materials provides a new method for the high-value utilization of titanium-based composite materials and carbon fibers.

CN119220913APending Publication Date: 2024-12-31KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411363914.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, there are few researches on the reinforcing phases of recovered carbon fibers for titanium-based composite materials, and the traditional heating methods are inefficient, making it difficult to effectively improve the mechanical properties and ductility of the material.

Method used

Modified and recovered carbon fibers are used to form efficient carbon fiber-reinforced titanium-based composite materials through electrochemical etching and microwave sintering. Microwave sintering is used to achieve rapid and efficient ceramic reinforced phase synthesis, improving the mechanical properties and ductility of the material.

Benefits of technology

It significantly improves the tensile strength and ductility of titanium-based composite materials, provides new ideas for the preparation technology of titanium-based composite materials, and provides an effective way for the high-value utilization of carbon fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220913A_ABST
    Figure CN119220913A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon fiber reinforced titanium-based composite material and a preparation method thereof, and belongs to the technical field of titanium-based composite material preparation, modified recycled carbon fibers and matrix powder are fully mixed and screened, the undersize mixture is subjected to cold press molding to obtain a green body, the green body is subjected to microwave sintering in an inert gas atmosphere, and the carbon fiber reinforced titanium-based composite material is obtained. And preparing to obtain the carbon fiber reinforced titanium-based composite material. According to the method, a microstructure is formed on the surface of the carbon fiber through a carbon fiber electrochemical etching surface treatment technology, so that the surface roughness and active functional groups of the carbon fiber are increased, the binding force of the carbon fiber and a matrix is improved, and the interface performance of the composite material can be remarkably improved. And reinforcing phase titanium carbide is more easily generated by recovering surface defects of the carbon source. According to the titanium-based composite material prepared through the method, the mechanical property and ductility of the material can be comprehensively improved, energy is saved, consumption is reduced, and meanwhile an effective way is provided for high-value utilization of recycled carbon fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium-based composite material preparation, and in particular relates to a carbon fiber reinforced titanium-based composite material and a preparation method thereof. Background Art

[0002] Discontinuously reinforced titanium matrix composites (DRTMCs) are lightweight, heat-resistant, high-strength, and deformable materials with broad application prospects in the aerospace field. This type of composite material can effectively improve the mechanical properties, wear resistance, high-temperature strength, and oxidation resistance of the titanium matrix by introducing discontinuous reinforcement phases such as ceramic particles and carbon materials into the titanium matrix.

[0003] The ceramic phase reinforced titanium-based composite material prepared by the in-situ synthesis method has small particle size, uniform distribution, clean and pollution-free interface between particles and matrix, ideal in-situ matching between the two, good interface bonding, and stable thermodynamic state of the reinforcement phase particles. At the same time, recent studies have shown that the in-situ synthesis method can be used to synthesize controllable size reinforcement phase nanoparticles in titanium alloys, which is a unique advantage of the in-situ synthesis method.

[0004] The selection of the reinforcement phase is crucial to the performance of the composite material. TiC particles in the reinforcement phase are the first choice due to their high hardness, good wear resistance, thermal stability and thermal expansion coefficient similar to that of titanium. Through reasonable design and preparation technology, the mechanical properties and application range of DRTMCs can be further improved. Recycled carbon fiber mainly comes from high-tech fields such as wind turbine blades and aircraft components. After the carbon fiber is separated by pyrolysis treatment and a series of treatments, it is obtained by recycled carbon fiber. Carbon fiber recycling technology is constantly developing to achieve sustainable utilization of resources and reduce the impact on the environment. At present, there are few reports on the use of recycled carbon fiber as the reinforcement phase of titanium-based composites. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon fiber reinforced titanium-based composite material and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.

[0006] One of the technical solutions provided by the present invention:

[0007] A method for preparing a carbon fiber reinforced titanium-based composite material comprises the following steps: fully mixing modified recycled carbon fiber and matrix powder, screening, cold-pressing the sieved mixture to obtain a green body, and microwave sintering the green body in an inert gas atmosphere to prepare the carbon fiber reinforced titanium-based composite material.

[0008] Preferably, the mass ratio of the modified recycled carbon fiber to the matrix powder is (0.1-10):(90-99.9).

[0009] Preferably, the cold pressing pressure during the cold pressing forming process is 400-700 MPa, and the cold pressing time is 5 minutes.

[0010] Preferably, the matrix powder is selected from pure titanium micropowder, pre-alloyed micropowder or single element micropowder constituting the alloy.

[0011] Preferably, the microwave sintering has a power of 2000-3000 W, a temperature of 1000-1200° C., and a sintering time of 120 min.

[0012] Microwave sintering is an efficient energy conversion process that is achieved through the interaction between polar molecules in the material and the microwave electromagnetic field. When polar molecules such as water are present in the medium, they will produce rapid rotation or vibration under the action of microwaves. As the electromagnetic field changes at a high frequency, the dipoles are constantly rearranged at an extremely high speed (hundreds of millions of times per second). This rearrangement and movement of molecules needs to overcome the thermal motion within the molecules and the interaction forces between molecules, thereby producing a friction-like effect. It is this friction between molecules that gradually converts the energy in the electromagnetic field into heat energy, causing a significant increase in the temperature of the medium. Microwave heating technology is usually faster and more efficient than traditional heating methods because it can generate heat directly inside the material.

[0013] The present invention adopts microwave sintering to in-situ synthesize ceramic reinforcement phase, which can further improve the mechanical properties and application range of DRTMCs, and can obtain a composite material with high strength while maintaining quite good ductility, providing a new idea for the technical field of titanium-based composite material preparation, and also providing a new way for the high-value utilization of recycled carbon fibers.

[0014] Preferably, the modified recycled carbon fiber is prepared by electrochemical etching using the recycled carbon fiber as an anode and platinum as a cathode in an electrolyte;

[0015] The recycled carbon fiber is recovered by a microwave heating method.

[0016] More preferably, the microwave heating method is divided into two stages: the first stage: the power is 600-800 W, the atmosphere is air, and the heating time is 20-30 min; the second stage: the power is 400-600 W, the atmosphere is argon, and the heating time is 40-50 min.

[0017] More preferably, the electrolyte is acidic or alkaline.

[0018] More preferably, the working voltage of the electrochemical etching is 5.5-6V, and the current density is 45-60mA / cm 2 , time is 5 to 10 minutes.

[0019] In the electrochemical etching process, the recycled carbon fiber is used as the anode, and the surface is etched and modified in the electrolyte through the anodic oxidation reaction and the stripping effect. The electrolyte is acidic or alkaline. When the electrolyte is acidic, it is obtained by mixing one or more of nitric acid, sulfuric acid or phosphoric acid. When the electrolyte is alkaline, it is obtained by mixing one or more of sodium hydroxide or potassium hydroxide solutions. The present invention accurately controls the etching process by controlling the current and voltage, realizes continuous processing, is simple to operate and has mild conditions.

[0020] The second technical solution provided by the present invention is:

[0021] A carbon fiber reinforced titanium-based composite material is prepared by the above preparation method.

[0022] Compared with the prior art, the present invention has the following advantages and technical effects:

[0023] The present invention chemically etches the recycled carbon fibers and adds them to the titanium-based composite material, which can provide a carbon source for in-situ synthesis of TiC ceramic reinforcement phases. The defects on the surface of the recycled carbon source are conducive to the occurrence of solid-solid reactions. The prepared titanium-based composite material has higher tensile strength and better ductility than pure titanium.

[0024] The present invention forms a microstructure on the surface of carbon fiber through the carbon fiber electrochemical etching surface treatment technology to increase its surface roughness and active functional groups, thereby improving the bonding force between the carbon fiber and the matrix, and can significantly improve the interface performance of the composite material. Recycling the surface defects of the carbon source makes it easier to generate reinforcing phase titanium carbide. The titanium-based composite material prepared by the present invention can comprehensively improve the mechanical properties and ductility of the material, while saving energy and reducing consumption, it also provides an effective way for the high-value utilization of recycled carbon fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 The process flow chart of preparing carbon fiber reinforced titanium-based composite material of the present invention;

[0027] Figure 2 This is the XRD pattern of the carbon fiber reinforced titanium-based composite material prepared in Example 1;

[0028] Figure 3 This is a SEM-EDS image of the carbon fiber reinforced titanium-based composite material prepared in Example 1;

[0029] Figure 4 is the SEM image of the recycled carbon fiber without electrochemical etching;

[0030] Figure 5 is a SEM image of the modified recycled carbon fiber in S1 in Example 1;

[0031] Figure 6 This is a microwave sintering heating curve in S3 in Example 1. DETAILED DESCRIPTION

[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] The room temperature in the present invention refers to 25±2°C.

[0038] In the embodiment of the present invention, a corresponding mass of powder raw material is weighed according to the ratio of the reinforcing phase and the matrix powder, wherein the reinforcing phase is a modified recycled carbon fiber, and the mechanical properties of the recycled carbon fiber are maintained at more than 90%. The reinforcing phase is placed in an electrolyte for electrochemical etching to increase its specific surface area. The reinforcing phase is then mixed with the matrix and sieved, and the sieved material is taken for cold pressing to obtain a green body. The obtained green body is placed in a quartz tube, wherein the silicon carbide plate is located directly below the quartz glass, and an inert gas is passed into the quartz glass tube to prevent the sample from being oxidized. Finally, the green body is heated to a certain temperature using a microwave and then cooled with the furnace to obtain a carbon fiber reinforced titanium-based composite material. Figure 1 The present invention is a process flow chart for preparing a carbon fiber reinforced titanium-based composite material.

[0039] Example 1 A method for preparing a carbon fiber reinforced titanium-based composite material

[0040] S1. The carbon fiber in the sucker rod was treated by microwave heating to obtain recycled carbon fiber, wherein the microwave heating method was divided into two stages, the first stage: the power was 600W, the atmosphere was air, and the heating time was 30min; the second stage: the power was 400W, the atmosphere was argon, and the heating time was 40min; the recycled carbon fiber was used as the anode and platinum was used as the cathode, and was placed in an electrolyte (sulfuric acid solution (18.4mol / L concentration) and nitric acid solution (8mol / L concentration) were mixed in a volume ratio of 3:1), the working voltage was 6V, and the current density was 45mA / cm 2 , electrochemical etching for 5 min, to prepare modified recycled carbon fiber as reinforcement phase;

[0041] S2. Weigh the modified recycled carbon fiber and pure titanium in a mass ratio of 1:99, put the raw material powders into a ball mill and mix them thoroughly, the ball-to-material ratio in the ball mill is 1:1.2, the ball milling time is 90 min, and then sieve, the sieve is 120 mesh, the sieve mixture is put into a mold for cold pressing to obtain a green body, the cold pressing pressure is 400 MPa, and the cold pressing time is 5 min;

[0042] S3. The obtained green body is placed in a quartz tube, wherein the silicon carbide plate is located directly below the quartz tube, high-purity argon is introduced into the quartz glass tube to prevent the sample from being oxidized, and finally the green body is heated and sintered by microwave (heating from room temperature to 1000°C for 50 minutes at a heating power of 2000W to 2200W, and kept at 1000°C for 120 minutes. During the keeping stage, the microwave is intermittently output and the keeping power is lower than the heating power), and then cooled in the furnace to obtain a carbon fiber reinforced titanium-based composite material.

[0043] The present invention uses a universal mechanical testing machine (US INSTRON 3367) to measure the properties of the composite material. The density of the carbon fiber reinforced titanium-based composite material prepared in this embodiment is 98.2%, the tensile strength is 720Mpa, the elongation after fracture is greater than or equal to 30%, and the sintering energy consumption is 3.7kW·h -1 .

[0044] Figure 2 This is the XRD diagram of the carbon fiber reinforced titanium-based composite material prepared in Example 1. The XRD test results show that the phases are Ti and TiC.

[0045] Figure 3 This is the SEM-EDS image of the carbon fiber reinforced titanium-based composite material prepared in Example 1. Analysis shows that the Ti element and the C element are evenly distributed and tightly combined;

[0046] Figure 4 is the SEM image of the recycled carbon fiber without electrochemical etching;

[0047] Figure 5 This is a SEM image of the modified recycled carbon fiber in S1 in Example 1; the specific surface area of ​​the electroplated and etched carbon fiber is 15% larger than that of the unetched one;

[0048] Figure 6 This is a microwave sintering heating curve in S3 in Example 1.

[0049] Example 2 A method for preparing a carbon fiber reinforced titanium-based composite material

[0050] S1. The carbon fiber in the sucker rod was treated by microwave heating to obtain recycled carbon fiber, wherein the microwave heating method was divided into two stages, the first stage: the power was 700W, the atmosphere was air, and the heating time was 25min, the second stage: the power was 500W, the atmosphere was argon, and the heating time was 50min; the recycled carbon fiber was used as the anode and platinum was used as the cathode, and was placed in an electrolyte (sulfuric acid solution (18.4mol / L concentration) and nitric acid solution (8mol / L concentration) were mixed in a volume ratio of 3:1), the working voltage was 5.7V, and the current density was 50mA / cm 2 , electrochemical etching for 7 min, to prepare modified recycled carbon fiber as reinforcement phase;

[0051] S2. Weigh the modified recycled carbon fiber and pure titanium at a mass ratio of 0.5:99.5, put the above raw material powders into a V-type mixer and mix them thoroughly for 2 hours, put the obtained materials into a sieve for screening, the sieve is 150 mesh, put the sieve mixture into a mold for cold pressing to obtain a green body, the cold pressing pressure is 500 MPa, and the cold pressing time is 5 minutes.

[0052] S3. The obtained green body is placed in a quartz tube, wherein the silicon carbide plate is located directly below the quartz tube, high-purity argon gas is introduced into the quartz glass tube to prevent the sample from being oxidized, and finally the green body is heated and sintered by microwave (heating from room temperature to 1000°C for 40 minutes at a heating power of 2500W, and kept at 1000°C for 120 minutes. During the insulation stage, the microwave is intermittently output and the insulation power is lower than the heating power), and then cooled in the furnace to obtain a carbon fiber reinforced titanium-based composite material.

[0053] The carbon fiber reinforced titanium-based composite material prepared in this embodiment has a density of 98.7%, a tensile strength of 742 MPa, an elongation after fracture of greater than or equal to 32%, and a sintering energy consumption of 3.9 kW·h -1 .

[0054] Example 3 Preparation method of carbon fiber reinforced titanium-based composite material

[0055] S1. The carbon fiber in the sucker rod was treated by microwave heating to obtain recycled carbon fiber, wherein the microwave heating method was divided into two stages, the first stage: the power was 800W, the atmosphere was air, and the heating time was 30min; the second stage: the power was 600W, the atmosphere was argon, and the heating time was 50min; the recycled carbon fiber was used as the anode and platinum as the cathode, and was placed in an electrolyte (sulfuric acid solution (18.4mol / L concentration) and nitric acid solution (8mol / L concentration) were mixed in a volume ratio of 3:1), the working voltage was 6V, and the current density was 60mA / cm 2 , electrochemical etching for 10 min, to prepare modified recycled carbon fiber as reinforcement phase;

[0056] S2. Weigh the modified recycled carbon fiber and titanium alloy TA15 in a mass ratio of 10:90, put the raw material powders into a ball mill and mix them thoroughly, the ball-to-material ratio in the ball mill is 2:1, the ball milling time is 120 min, and then screened, the screen is 150 mesh, the screened mixture is put into a mold for cold pressing to obtain a green body, the cold pressing pressure is 600 MPa, and the cold pressing time is 5 min;

[0057] S3. The obtained green body is placed in a quartz tube, wherein the silicon carbide plate is located directly below the quartz tube, high-purity argon is introduced into the quartz glass tube to prevent the sample from being oxidized, and finally the green body is heated and sintered by microwave (heating from room temperature to 1100°C for 65 minutes at a heating power of 3000 W, and kept at 1100°C for 120 minutes. During the insulation stage, the microwave is intermittently output and the insulation power is lower than the heating power), and cooled in the furnace to obtain a carbon fiber reinforced titanium-based composite material.

[0058] The carbon fiber reinforced titanium-based composite material prepared in this embodiment has a density of 98.9%, a tensile strength of 1250 MPa, an elongation after fracture of greater than or equal to 15%, and a sintering energy consumption of 4.8 kW·h -1 .

[0059] Example 4 A method for preparing a carbon fiber reinforced titanium-based composite material

[0060] S1. The carbon fiber in the sucker rod was treated by microwave heating to obtain recycled carbon fiber, wherein the microwave heating method was divided into two stages, the first stage: the power was 800W, the atmosphere was air, and the heating time was 30min; the second stage: the power was 600W, the atmosphere was argon, and the heating time was 50min; the recycled carbon fiber was used as the anode and platinum as the cathode, and was placed in an electrolyte (sulfuric acid solution (18.4mol / L concentration) and nitric acid solution (8mol / L concentration) were mixed in a volume ratio of 3:1), the working voltage was 6V, and the current density was 60mA / cm 2 , electrochemical etching for 10 min, to prepare modified recycled carbon fiber as reinforcement phase;

[0061] S2. Weigh the modified recycled carbon fiber and titanium alloy TC4 according to the mass ratio of 0.1:99.9, put the raw material powder into a ball mill and mix them thoroughly, the ball-to-material ratio in the ball mill is 3:1, the ball milling time is 150min, and then screened, the screen is 200 mesh, the screened mixture is put into a mold for cold pressing to obtain a green body, the cold pressing pressure is 700Mpa, and the cold pressing time is 5min;

[0062] S3. The obtained green body is placed in a quartz tube, wherein the silicon carbide plate is located directly below the quartz tube, high-purity argon is introduced into the quartz glass tube to prevent the sample from being oxidized, and finally the green body is heated and sintered by microwave (heating from room temperature to 1200°C for 80 minutes at a heating power of 3000 W, and kept at 1100°C for 120 minutes. During the insulation stage, the microwave is intermittently output and the insulation power is lower than the heating power), and cooled in the furnace to obtain a carbon fiber reinforced titanium-based composite material.

[0063] The carbon fiber reinforced titanium-based composite material prepared in this embodiment has a density of 99.2%, a tensile strength of 1200 MPa, an elongation after fracture of greater than or equal to 13%, and a sintering energy consumption of 5.9 kW·h -1 .

[0064] Comparative Example 1

[0065] S1. The carbon fiber in the sucker rod was treated by microwave heating to obtain recycled carbon fiber, wherein the microwave heating method was divided into two stages, the first stage: the power was 600W, the atmosphere was air, and the heating time was 30min; the second stage: the power was 400W, the atmosphere was argon, and the heating time was 40min; the recycled carbon fiber was used as the anode and platinum was used as the cathode, and was placed in an electrolyte (sulfuric acid solution (18.4mol / L concentration) and nitric acid solution (8mol / L concentration) were mixed in a volume ratio of 3:1), the working voltage was 6V, and the current density was 45mA / cm 2 , electrochemical etching for 5 min, to prepare modified recycled carbon fiber as reinforcement phase;

[0066] S2. Weigh the modified recycled carbon fiber and pure titanium at a mass ratio of 1:99, put the raw material powders into a V-type mixer and mix them thoroughly for 2 hours, put the obtained materials into a sieve for sieving, the sieve is 120 mesh, put the mixture under the sieve into a mold for cold pressing to obtain a green body, the cold pressing pressure is 400Mpa, and the cold pressing time is 5min;

[0067] S3. The obtained green body is placed in a conventional muffle furnace for heating and sintering. High-purity argon gas is introduced to prevent the sample from being oxidized. The gas flow rate is 25 mL / min. The time for heating from room temperature to 1000°C is 195 min and sintering is performed at 1000°C for 120 min. The sample is cooled in the furnace to obtain a carbon fiber reinforced titanium-based composite material.

[0068] Compared with the carbon fiber reinforced titanium-based composite material obtained in Example 1, the energy consumption of this comparative example is higher and the heating rate is slower. The external temperature of the sample is higher than the internal temperature. The temperature difference between the inside and outside of the sample is large, and the sample is heated unevenly. The time for heating from room temperature to 1000°C is about 120 minutes. The density of the sintered material is 92.3%, the tensile strength is 592Mpa, the elongation after fracture is greater than or equal to 21%, and the sintering energy consumption is 5.6kW·h -1 .

[0069] Compared with Example 1, this comparative example proves that microwave sintering has the effect of increasing the density of the material and thus improving the mechanical properties of the material.

[0070] Comparative Example 2

[0071] S1. Select the purchased chopped carbon fiber (Japan Deyan T300 carbon fiber powder) as the anode and platinum as the cathode, put it into the electrolyte (sulfuric acid solution (18.4 mol / L concentration) and nitric acid solution (8 mol / L concentration) mixed in a volume ratio of 3:1), the working voltage is 6V, and the current density is 45mA / cm 2 , electrochemical etching for 5 min, to prepare modified carbon fiber as reinforcement phase;

[0072] S2. Weigh the modified carbon fiber and pure titanium in a mass ratio of 1:99, put the raw material powder into a V-type mixer and mix them thoroughly. The mixing time is 2 hours. Put the obtained material into a sieve for sieving. The sieve is 150 mesh. Put the mixture under the sieve into a mold for cold pressing to obtain a green body. The cold pressing pressure is 300 MPa and the cold pressing time is 5 minutes.

[0073] S3. The obtained green body is placed in a conventional muffle furnace for heating and sintering. High-purity argon gas is introduced to prevent the sample from being oxidized. The gas flow rate is 25 mL / min. The time for heating from room temperature to 1000°C is 195 min and sintering is performed at 1000°C for 120 min. The sample is cooled in the furnace to obtain a carbon fiber reinforced titanium-based composite material.

[0074] The carbon fiber reinforced titanium-based composite material prepared in this comparative example has a density of 91.5% after sintering, a tensile strength of 585 MPa, an elongation after fracture of greater than or equal to 19.2%, and a sintering energy consumption of 5.6 kW·h -1 .

[0075] Compared with Example 1, this comparative example proves that the recycled carbon fiber combined with microwave sintering has the effect of improving the density of the material and thus improving the mechanical properties of the material.

[0076] Comparative Example 3

[0077] S1. The carbon fibers in the sucker rod were treated by microwave heating to obtain recycled carbon fibers, wherein the microwave heating method was divided into two stages: the first stage: the power was 700 W, the atmosphere was air, and the heating time was 25 min; the second stage: the power was 500 W, the atmosphere was argon, and the heating time was 50 min;

[0078] S2. Recycled carbon fiber and pure titanium were weighed at a mass ratio of 0.5:99.5, and the raw material powders were placed in a V-type mixer and mixed thoroughly for 2 hours. The obtained material was placed in a sieve for sieving, and the sieve was selected to be 150 mesh. The mixture under the sieve was placed in a mold for cold pressing to obtain a green body, and the cold pressing pressure was 300 MPa and the cold pressing time was 5 min;

[0079] S3. The obtained green body is placed in a conventional muffle furnace for heating and sintering. High-purity argon gas is introduced to prevent the sample from being oxidized. The gas flow rate is 25 mL / min. The time for heating from room temperature to 1000°C is 195 min and sintering is performed at 1000°C for 120 min. After cooling in the furnace, a carbon fiber reinforced titanium-based composite material is obtained.

[0080] The carbon fiber reinforced titanium-based composite material prepared in this comparative example has a density of 91.6%, a tensile strength of 576 MPa, an elongation after fracture of greater than or equal to 18.7%, and a sintering energy consumption of 5.6 kW·h -1.

[0081] Compared with Example 2, this comparative example proves that electrochemical etching combined with microwave sintering has the effect of improving the density of the material and thus improving the mechanical properties of the material.

[0082] Comparative Example 4

[0083] S1. Take the purchased chopped carbon fiber (Japan Deyan T300 carbon fiber powder) and titanium alloy TA15 in a mass ratio of 10:90, put the above raw material powder into a ball mill and mix them thoroughly, the ball-to-material ratio in the ball mill is 2:1, the ball milling time is 120min, and then sieve, the sieve is selected to be 150 mesh, put the sieve mixture into a mold for cold pressing to obtain a green body, the cold pressing pressure is 600Mpa, and the cold pressing time is 5min;

[0084] S2. The obtained green body is placed in a conventional muffle furnace for heating and sintering. High-purity argon gas is introduced to prevent the sample from being oxidized. The gas flow rate is 25 mL / min. The time for heating from room temperature to 1100°C is 245 min and sintering is performed at 1100°C for 120 min. After cooling in the furnace, a carbon fiber reinforced titanium-based composite material is obtained.

[0085] The carbon fiber reinforced titanium-based composite material prepared in this comparative example has a density of 90.7%, a tensile strength of 522 MPa, an elongation after fracture of greater than or equal to 19%, and a sintering energy consumption of 5.6 kW·h -1 .

[0086] Compared with Example 1, this comparative example proves that microwave sintering combined with electrochemical etching and recycled carbon fiber has the effect of improving the density of the material and thus improving the mechanical properties of the material.

[0087] Comparative Example 5

[0088] S1. The carbon fibers in the sucker rod were treated by microwave heating to obtain recycled carbon fibers, wherein the microwave heating method was divided into two stages: the first stage: the power was 600 W, the atmosphere was air, and the heating time was 30 min; the second stage: the power was 400 W, the atmosphere was argon, and the heating time was 40 min;

[0089] S2. The recycled carbon fiber and pure titanium prepared in S1 were weighed at a mass ratio of 1:99, and the raw material powders were put into a ball mill and mixed thoroughly. The ball-to-material ratio in the ball mill was 1:1.2, and the ball milling time was 90 min. Then, the mixture was sieved, and a 120-mesh sieve was selected. The mixture under the sieve was put into a mold for cold pressing to obtain a green body. The cold pressing pressure was 400 MPa, and the cold pressing time was 5 min.

[0090] S3. Same as Example 1.

[0091] The carbon fiber reinforced titanium-based composite material prepared in this comparative example has a density of 96.2%, a tensile strength of 686 MPa, an elongation after fracture of greater than or equal to 27%, and a sintering energy consumption of 3.7 kW·h -1 .

[0092] Compared with Example 1, this comparative example proves that electrochemical etching has the effect of increasing the surface area of ​​the reinforcement and thus improving the mechanical properties of the material.

[0093] Comparative Example 6

[0094] S1. Select the purchased chopped carbon fiber (Japan Deyan T300 carbon fiber powder) as the anode and platinum as the cathode, put it into the electrolyte (sulfuric acid solution (18.4 mol / L concentration) and nitric acid solution (8 mol / L concentration) mixed in a volume ratio of 3:1), the working voltage is 6V, and the current density is 45mA / cm 2 , electrochemical etching for 5 min, to prepare modified carbon fiber as reinforcement phase;

[0095] S2. The modified carbon fiber and pure titanium prepared in S1 were weighed at a mass ratio of 1:99, and the raw material powders were put into a ball mill and mixed thoroughly. The ball-to-material ratio in the ball mill was 1:1.2, and the ball milling time was 90 min. Then, the mixture was sieved, and the sieve was selected to be 120 mesh. The mixture under the sieve was put into a mold for cold pressing to obtain a green body. The cold pressing pressure was 400 MPa, and the cold pressing time was 5 min.

[0096] S3. Same as Example 1.

[0097] The carbon fiber reinforced titanium-based composite material prepared in this comparative example has a density of 97.6%, a tensile strength of 700 MPa, an elongation after fracture of greater than or equal to 28.7%, and a sintering energy consumption of 3.7 kW·h -1 .

[0098] Compared with Example 1, this comparative example proves that the mechanical properties of microwave-recycled carbon fiber are not much different from those of commercial carbon fiber, providing an effective way to high-value utilization of recycled carbon fiber.

[0099] Comparative Example 7

[0100] S1. Weigh the purchased chopped carbon fiber (Japan Deyan T300 carbon fiber powder) and titanium alloy TC4 according to the mass ratio of 0.1:99.9, put the above raw material powder into a ball mill and mix them thoroughly. The ball-to-material ratio in the ball mill is 3:1, and the ball milling time is 150min. Then, sieve the mixture with a 200-mesh screen. Put the mixture under the sieve into a mold for cold pressing to obtain a green body. The cold pressing pressure is 700Mpa and the cold pressing time is 5min.

[0101] S2. Same as Example 4

[0102] The carbon fiber reinforced titanium-based composite material prepared in this example has a density of 96.1%, a tensile strength of 1025 MPa, an elongation after fracture greater than or equal to 10%, and a sintering energy consumption of 5.9 kW·h. Compared with Example 4, this comparative example proves the effect of microwave recovery of carbon fiber combined with electrochemical etching to increase the relative surface area of ​​the reinforcement to generate TiC and thus improve the mechanical properties of the material.

[0103] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a carbon fiber reinforced titanium-based composite material, characterized in that: The following steps are involved: The modified recycled carbon fiber and the matrix powder are fully mixed and sieved, the sieved mixture is cold pressed to obtain a green body, and the green body is microwave sintered in an inert gas atmosphere to prepare the carbon fiber reinforced titanium-based composite material.

2. The method for preparing a carbon fiber reinforced titanium-based composite material according to claim 1, characterized in that: The mass ratio of the modified recycled carbon fiber to the matrix powder is (0.1-10): (90-99.9).

3. The method for preparing a carbon fiber reinforced titanium-based composite material according to claim 1, characterized in that: The cold pressing pressure during the cold pressing forming process is 400-700Mpa, and the cold pressing time is 5 minutes.

4. The method for preparing a carbon fiber reinforced titanium-based composite material according to claim 1, characterized in that: The matrix powder is selected from pure titanium micropowder, pre-alloyed micropowder or single element micropowder constituting the alloy.

5. The method for preparing a carbon fiber reinforced titanium-based composite material according to claim 1, characterized in that: The microwave sintering has a power of 2000-3000W, a temperature of 1000-1200°C and a time of 120 minutes.

6. The method for preparing a carbon fiber reinforced titanium-based composite material according to claim 1, characterized in that: The preparation method of the modified recycled carbon fiber is as follows: using the recycled carbon fiber as an anode and platinum as a cathode, placing them in an electrolyte, and preparing them by electrochemical etching; The recycled carbon fiber is recovered by a microwave heating method.

7. The method for preparing a carbon fiber reinforced titanium-based composite material according to claim 6, characterized in that: The microwave heating method is divided into two stages: the first stage: the power is 600-800W, the atmosphere is air, and the heating time is 20-30min; the second stage: the power is 400-600W, the atmosphere is argon, and the heating time is 40-50min.

8. The method for preparing a carbon fiber reinforced titanium-based composite material according to claim 6, characterized in that: The electrolyte is acidic or alkaline.

9. The method for preparing a carbon fiber reinforced titanium-based composite material according to claim 6, characterized in that: The working voltage of the electrochemical etching is 5.5-6V, and the current density is 45-60mA / cm 2 , time is 5 to 10 minutes.

10. A carbon fiber reinforced titanium-based composite material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9.